2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--3604
|View full text |Cite
|
Sign up to set email alerts
|

Liberal Education: A Survey Of Goals

Abstract: and chair of its Department of Mechanical and Civil Engineering. He received both his PhD and BS degrees in Civil Engineering from the University of Missouri Rolla and his MS degree from the University of Florida. He is a registered professional engineer in several states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They concluded that administrators view liberal learning as a path to prepare students to become productive professionals, community citizens, and leaders in a diverse and socially dynamic world. Further, there is ample evidence that liberal learning outcomes are most effectively achieved when undertaken as a partnership between the often separated curricular spheres of general education and the major (Valenzuela, Allen, & Swenty, 2008).…”
mentioning
confidence: 99%
“…They concluded that administrators view liberal learning as a path to prepare students to become productive professionals, community citizens, and leaders in a diverse and socially dynamic world. Further, there is ample evidence that liberal learning outcomes are most effectively achieved when undertaken as a partnership between the often separated curricular spheres of general education and the major (Valenzuela, Allen, & Swenty, 2008).…”
mentioning
confidence: 99%
“…Many educators also believe that the inclusion of liberal arts education within an engineering degree is critical to help our students become better people and better community members, not just better engineers (e.g., [38], [39] ). Our work on integrated education has the potential to equally address this goal and the goal of educating more competent professionals.…”
Section: The Liberal Arts and Engineering Educationmentioning
confidence: 99%